Efficient synthesis of high solid content emulsions of AIE polymeric nanoparticles with tunable brightness and surface functionalization through miniemulsion polymerization. (April 2019) - Liang, Xiaoqin; Hu, Yaxin; Cao, Zhihai; Xiao, Lisheng; Lou, Junjie; Liu, Ling; Wang, Yijia; Zhao, Zujin; Qi, Dongming; Cui, Qinmin
Abstract: Efficient production and flexible surface functionalization are important developing directions for the synthesis of polymeric nanomaterials. In this work, aggregation-induced emission (AIE) polymeric nanoparticles (PNPs) were efficiently synthesized by encapsulating a model AIE luminogen, tetraphenylethylene (TPE), within a polymeric matrix via miniemulsion polymerization. The AIE PNPs with similar emission and particle properties were synthesized in a wide solid content range of 8–40 wt%. The particle size and photoluminescence intensity of AIE PNPs could be flexibly tuned by synthetic parameters including the surfactant content and TPE content. Furthermore, the surface carboxyl- and amino-functionalization of AIE PNPs were conveniently achieved through copolymerization of styrene and functional monomers methacrylic acid and 2-aminoethyl methacrylate hydrochloride, respectively, in miniemulsions. The surface functionalization extent could be facilely tuned by the content of functional monomers. This miniemulsion polymerization based technique could be a feasible and efficient method to prepare AIE PNPs with versatile surface functionalization, tunable brightness, and controllable particle properties for the applications in biodetection, bioimaging, etc. Graphical abstract: Highlights: AIE PNPs can be efficiently made via high solid content miniemulsion polymerization. Surface functionalization of AIE PNPs can be directly performed during polymerization. Brightness, particle properties, and surface functionalization of AIE PNPs can be facilely tuned.